Metal silylenes generated by double silicon-hydrogen activation: key intermediates in the rhodium-catalyzed hydrosilylation of ketones : dedicated to Professor Helmut Werner on the occasion of his 75th birthday - Schneider, Nathanaëlle; Finger, Markus; Haferkemper, Christian; Bellemin-Laponnaz, Stéphane; Hofmann, Peter; Gade, Lutz H. (Angewandte Chemie. International edition, 2009)
Rhodium silylenes, which are generated by double Si-H activation at the metal, are involved in a low-activation-barrier mechanism of the hydrosilylation of ketones with R2SiH2. A DFT-based study of reaction mechanisms accounts for the experimental observations, notably the rate enhancement for R2SiH2 over R3SiH and an inverse kinetic isotope effect.
First published: 10 February 2009
Gesehen am 07.12.2022
Keywords: Festschrift